The potential role of assisted oocyte activation in the management of a POSEIDON group 3 patient with fertilization failure: A case report and literature review - Tian-Chi Tsai; Huan-Ka Chiung; Liang-Hsuan Chen; Hsien-Ming Wu (Elsevier, 2021)
Objective: Assisted oocyte activation combined with ICSI (ICSI-AOA) has been reported to improve fertilization outcomes of couples with oocyte activation deficiency (OAD). Although there's no sufficient evidence to support ICSI-AOA as routine use, it might be beneficial for POSEIDON group 3 patients with suspected oocyte-related OAD. Case report: A 29-year-old female presented with a history of primary infertility for two years. She was classified as a POSEIDON group 3 patient and had a total fertilization failure history. With the help of ICSI-AOA, six oocytes were successfully fertilized. Pregnancy was later confirmed after embryo transfer. A living infant was born after 34 weeks of pregnancy. Conclusion: OAD should be taken into consideration for POSEIDON group 3 patients since low Antimüllerian hormone is associated decreased quality. Further research needs to be done to understand the mechanism underlying oocyte-related OAD and the potential role of ICSI-AOA in young patients with suboptimal ovarian response.